Analisis Indeks Kinerja Jaringan Saluran Irigasi Studi Kasus Irigasi Sungai Siulak Deras Kabupaten Kerinci - Umar, Abdullah; Das, Amsori M.; Setiawan, Ari (Jurnal Civronlit Unbari, 2024)
The Siulak Deras Irrigation canal network is the main source of water distribution in several areas. The Siulak Deras Irrigation Area in Kerinci Regency was built in 1993 with water flow regulation and complete Siulak Deras Irrigation network facilities including the Technical irrigation group. As time goes by, the service function of the irrigation network experiences a decline in performance, so that operation and maintenance of the irrigation network is an activity that is really needed to make the irrigation network remain optimal and maintain its performance. In this regard, an assessment of the Performance Index of the irrigation system in the Siulak Deras Irrigation Area needs to be carried out to determine the value of aspects or components that are not yet optimal in this irrigation area so that special treatment can be immediately carried out or improved. The assessment is carried out by starting an inventory of the condition and function of the physical infrastructure of the irrigation network, planting productivity results, supporting facilities, organization, documentation and institutional P3A to determine the performance value and recommendations for handling it. The results of the irrigation network system performance index in the Siulak Deras irrigation area for the Left Irrigation Channel section are 69.59%, which means that the irrigation system performance is close to good performance, namely 70%, but still needs to be improved and needs attention. With a physical infrastructure value of 29.32%, planting productivity 14.21%, supporting facilities 6.15%, personnel organization 10.94%, documentation 2.46%, and P3A institutions 6.50%. Based on the performance index value obtained, and the total performance score in the form of a percentage, it is necessary to specifically maintain and repair physical facilities and infrastructure at several points that are damaged, facilitate supporting facilities for OP officers so that officers can act quickly and precisely in carrying out activities, and paying more attention to P3A so that it can always contribute to maintaining and utilizing the Siulak Deras irrigation network properly and optimally in the future.